Respuesta :

Answer:

The answer is "[tex]AB= \left[\begin{array}{cc} -2 &51 \\-8&33\\0&27&\end{array}\right][/tex]"

Step-by-step explanation:

If the value of A and B is:

[tex]A= \left[\begin{array}{cc}-1&6\\-4&5\\0&3\end{array}\right][/tex]

[tex]B=\left[\begin{array}{cc}2&3\\0&9\end{array}\right][/tex]

Find the value of A[tex]\times[/tex]B:

[tex]AB =\left[\begin{array}{cc}-1 \times 2+6 \times 0 &-1 \times 3+6 \times 9\\ -4 \times 2+5 \times 0& -4 \times 3+5 \times 9\\ 0 \times 2+3 \times 0&-1 \times 2+3\times 9\end{array}\right] \\ \\\\AB =\left[\begin{array}{cc}-2+0 &- 3+54\\ -8+0& -12+45\\ 0+ 0&-2 +27\end{array}\right] \\ \\[/tex]

[tex]AB= \left[\begin{array}{cc} -2 &51 \\-8&33\\0&27&\end{array}\right][/tex]